Effect of Foliar Micronutrient Application on Phytoconstituents and Mineral Composition of Carrot Grown in Trans-Himalayan Region - Tiwari, Vivek Kumar; Verma, Vivek; Avantika, Avantika; Mishra, Alok; Prasher, Diksha; Chaurasia, O. P.; Kathayat , Khushboo (Defence Life Science Journal, 2024)
The cropping season in trans-Himalayan region of Ladakh is limited to six months. Soil in the region is sandy, coarse textured, pH 7.79±0.2 and deficient in micronutrients. Carrot is one of the major root vegetable crops growing in this region. Therefore, a study investigating the effects of mineral supply on the nutritional quality (phytoconstituents and micronutrients) of carrot roots was undertaken. Maximum values of carotene and total flavonoids were recorded under the foliar application of ZnSO4 @ 0.5 % (T3), which was at par with application of ZnSO4 @ 1.0 % (T4). However, the maximum value of total phenol concentration (6.59±0.34 mg GAE/g DW) was recorded under foliar application of ZnSO4 @ 1.0 % (T4), which was at par with ZnSO4 @ 0.5 % (T3). Zinc and boron application influenced the mineral content of carrots. During plant growth, adding small amounts of zinc and boron to the feeding solutions affected the Cu, Mn and Zn concentration, in roots. Applying different amounts of minerals nutrients has the potential to improve the nutritional value and morpho-physical quality of carrots. This present study will help to understand the utilisation of optimal quantity of micronutrients to improve carrot cultivation in cold desert of Ladakh. Taking into consideration of variables like soil micronutrient deficiencies, this research opens the door to the biofortification of necessary minerals in crops.